2015
DOI: 10.1002/chem.201503063
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Scaffold‐Inspired Asymmetric Synthesis of Polysubstituted Chiral Hexahydropyridazines that Potently Inhibit Breast Cancer Cell Proliferation by Inducing Apoptosis

Abstract: The highly enantioselective preparation of pharmacologically interesting hexahydropyridazine derivatives based on a multicomponent cascade reaction is described. This one-pot approach utilizes an organocatalytic Michael reaction followed by intermolecular α-amination and intramolecular hemiaminalization to yield a chiral pyridazine backbone with contiguous stereogenic centers and multiple functional groups in good yield and with high stereoselectivity. Compounds synthesized by this method potently inhibited pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 73 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Real‐time PCR and Western blot analysis were performed according to our previous report . More information is provided in the “Data ”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐time PCR and Western blot analysis were performed according to our previous report . More information is provided in the “Data ”.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure of Nile red‐stained or TUNEL‐stained SEB‐1 cells, and the IHC‐stained skin tissue sections were stained according to our previous report . More information is provided in the “Data ”.…”
Section: Methodsmentioning
confidence: 99%
“…In order to assess the possibility of subroutine cell death underlying 8m treatment, flow cytometry with annexinV/PI dual staining was used to assess the activation of apoptosis [39][40][41][42][43][44][45] . Hoechst 33258 staining also clearly showed that nuclear morphological changes in apoptotic cells, including chromatin condensation and apoptotic bodies, mediated apoptosis ( Figure 5(D)).…”
Section: Novel Hsp90/pi3ka Dual Inhibitors 8m Suppressed Cell B16 Melmentioning
confidence: 99%
“…However, radiation resistance remains a major obstacle to successful treatment of advanced NPC. The detailed mechanism by which NPC develops radiation resistance and metastatic recurrence remains unclear [ 10 13 ]. Hence, the identification of novel prognostic biomarkers and therapeutic targets is urgently needed for NPC patients.…”
Section: Introductionmentioning
confidence: 99%